2016
DOI: 10.1002/htj.21230
|View full text |Cite
|
Sign up to set email alerts
|

Energy and Exergy Analysis of a Single-Pass Sequenced Array Baffled Solar Air Heater with Packed Bed Latent Storage Unit for Nocturnal Use

Abstract: The current study presents an experimental investigation on evaluation of thermal performance of a single-pass double-glazed solar air heater with the use of packed bed paraffin wax as a phase change material (PCM). Moreover, the absorber plate is equipped with baffles attached over its top. Galvanized sheets with a thickness of 0.4 mm and total surface areas of 30 cm 2 are chosen as baffles that are placed in a sequential manner over the absorber plate. The solar energy was stored in the packed bed PCM during… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 36 publications
0
12
0
Order By: Relevance
“…Ghiami et al 56 studied the single-channel SAT, as shown in Figure 14, the energy and exergy analysis of the SAT with LHTES shows that the daily energy efficiency ratio is 10.7% to 26.8%, and the daily exergy ratio is 10.7% to 19.5%.…”
Section: Stc S Integrated With Pcm For Heating Ventilation and Air mentioning
confidence: 99%
See 2 more Smart Citations
“…Ghiami et al 56 studied the single-channel SAT, as shown in Figure 14, the energy and exergy analysis of the SAT with LHTES shows that the daily energy efficiency ratio is 10.7% to 26.8%, and the daily exergy ratio is 10.7% to 19.5%.…”
Section: Stc S Integrated With Pcm For Heating Ventilation and Air mentioning
confidence: 99%
“…The innovative thermal hydraulic efficiency of the designed system is 79%, which is about 13% higher than the similar single duct design. Ghiami et al 56 studied the single‐channel SAT, as shown in Figure 14, the energy and exergy analysis of the SAT with LHTES shows that the daily energy efficiency ratio is 10.7% to 26.8%, and the daily exergy ratio is 10.7% to 19.5%.…”
Section: Stc Integrated With Pcmsmentioning
confidence: 99%
See 1 more Smart Citation
“…This thermal behavior of the PCM has been established in relationship with its position within the system. For example, Ndukwu et al [4] placed the PCM on the solar collector chamber during charging and moved it into the drying chamber during discharging in a solar dryer, while Ortega and Carmona [12] and Ghiami et al [13] placed their PCMs under the collector as shown in Figure 2. Nkwetta, and Haghighat [14] encapsulated the PCM in the solar system while Li et al [15] placed the PCM in a storage tank.…”
Section: Introductionmentioning
confidence: 99%
“…Ghiami et al 59 presented an experimental investigation on the evaluation of the thermal performance of a single‐pass double‐glazed solar air heater with the use of packed bed paraffin wax as a phase change material (PCM). Moreover, the absorber plate was equipped with baffles attached over its top.…”
Section: Introductionmentioning
confidence: 99%